Perspective of nursing students about active learning and insertion in the job market - Pinto, Adriana Avanzi Marques; Marin, Maria José Sanches [UNESP] (FapUNIFESP (SciELO), 2021)
OBJECTIVE: to understand the perception of alumni from a nursing course which uses active learning methods about their insertion in the job market. METHODS: descriptive and exploratory study with a qualitative approach, carried out through 17 interviews with alumni from 2012 and 2014. The analysis took place using Dialectic Hermeneutics, as subsidized by the theoretical framework of the Theory of Complexity. RESULTS: the statements of the alumni showed aspects related to safety to act in the job market, to stimulating proactivity and initiative for learning as proposed by the active method, to difficulties in teamwork, and to the lack of experience in certain specialized fields. FINAL CONSIDERATIONS: there are advances and challenges marked by contradictions in the way the alumni act and think as they enter the job market, which is an inherent condition to processes of change, from the perspective of complex thinking.